2015
DOI: 10.1186/1687-9856-2015-4
|View full text |Cite|
|
Sign up to set email alerts
|

A randomized pilot trial of growth hormone with anastrozole versus growth hormone alone, starting at the very end of puberty in adolescents with idiopathic short stature

Abstract: BackgroundWhen given during the course of puberty, anastrozole (A), an aromatase inhibitor, has been shown to increase the predicted adult height (PAH) of GH-deficient (GHD) boys treated with recombinant human growth hormone (rhGH). Our study questioned whether this treatment could retain some of its effects in non-GHD adolescent boys if started only at the very end of puberty, a time when rhGH treatment is denied to short adolescents who have almost reached their final height.ObjectiveTo explore the effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 94 publications
2
17
0
Order By: Relevance
“…In other recent studies the impact of AIs and or GH was also evaluated throughout NF height. Mauras et al [14] studied 25 ISS patients treated with AIs (ANZ or LTZ) and 26 ISS patients treated with AIs plus GH. The authors found after two years of treatment a height SDS increment (for chronological age) of 0.5 and 1.0, respectively for AI alone or combined with GH.…”
Section: Near-final Heightmentioning
confidence: 99%
“…In other recent studies the impact of AIs and or GH was also evaluated throughout NF height. Mauras et al [14] studied 25 ISS patients treated with AIs (ANZ or LTZ) and 26 ISS patients treated with AIs plus GH. The authors found after two years of treatment a height SDS increment (for chronological age) of 0.5 and 1.0, respectively for AI alone or combined with GH.…”
Section: Near-final Heightmentioning
confidence: 99%
“…However, the predicted FAH following a short period of treatment is dynamic and cannot reflect the actual FAH. Owing to the heterogeneity of the treated ISS populations and the individualization of treatment, only a few randomized trials with small sample sizes have observed ISS until FAH [6][7][8][9][10]. A randomized study of FAH typically takes 8 years or more to complete and is often difficult to implement in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…The same subjects were followed until near final height [7] and the boys treated with AI attained a mean NAH 6.7 cm higher compared to the control group. Subsequent studies were done in patients with ISS and GHD [8,10,11]. Hero et al [8] in a prospective doubleblinded, randomized, placebo controlled study showed that subjects with ISS treated with Letrozole have an increased PAH by 5.9 cm and height SD score for bone age increased by 0.7 SD score.…”
Section: Discussionmentioning
confidence: 99%
“…Also Rothenbuhler et al [11] conducted a prospective randomized study to compare GH alone and GH and Anastrozole in 24 adolescent boys with ISS who achieved NAH. Height gain compared to the pretreatment PAH was +4.6 cm greater and height SDS at NAH was +0.7 SD score greater in the subjects treated with GH and Anastrozole compared to the GH alone group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation